Ta’lim al-Imla’ bi Al-Wasit al-Muta’addidah li Tarqiyyah Maharah al-Kitabah fi al-Lughah al-‘Arabiyyah - Wijaya, Ida Suryani; Pimada, Luluk Humairo (Jurnal Al Bayan : Jurnal Jurusan Pendidikan Bahasa Arab, 2019)
Learning Arabic for writing skills is a skill at the highest level in language proficiency, even writing skills in Arabic must start to knowing the correct writing conventions especially in Arabic writing, because it will affect the order of meaning if the writing is not in accordance with the proper Arabic language rules, and the Arabic language rules are known as imla learning material. This research aims to find out the ability of writing in the subject of Imla’ and the influence  of the use of multimedia in Imla’ learning to improve the writing ability of the fifth semester students of Arabic Education Department of Teacher Training and Education Faculty of State Islamic Institute of Samarinda in the year of 2017-2018. And than the research uses a quantitative approach and the research method is an experiment with the ability test design of pre- test and post-test. The control class consisted of 25 students and the experimental class consisted of 25 students. The data analysis technique from both groups, the researcher used statistical calculation with the significant level  and used statistical formula of test T-test with the result of thit > ttab = 6،81 > 1،645. The results of research on the use multimedia in Arabic learning the material of Imla’ to improve the writing ability to have an impact effective, until can help the teacher and the learner to easily understand the rule of Arabic writing correctly as the rule of the Arabic writing.